Energy Efficiency of Rotor Application in Cyclone Dust Collector - V. V. Kuzmin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A method for increase of cyclone dust collector efficiency is proposed in the paper. The results of experimental investigations of hydraulic resistance and specific energy consumption for purification of gas flow in a new cyclone design are given in the paper.